Analisis Dana Perimbangan Kaitannya Dengan Percepatan Laju Pertumbuhan Ekonomi Kabupaten Lombok Timur Nusa Tenggara Barat Tahun 2012-2016 - Fatimah, Siti (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
In line of the authority which are owned by each region in the era of regional autonomy so the rule and function of regional income trough extracting potential of each region is very important, as an illustration the role of balance fund become strategic in the push the growth economic rate of region, the research aim is to see how the role of balance fund toward acceleration rate of economic growth east Lombok district since 2012-2016, to measure how high the contribution of fund balance toward total regional income which related to acceleration rate of economic growth east Lombok district since 2012-2016, this is descriptive research , data collecting technique use library research and field research variable done by regional income, fund balance, and other income , apparatus expenditure, service public expenditure, and profit sharing expenditure and analysis device ratio approach with compare the magnitude of fund balance with regional income also PDRB approach , also other component related with rate of economic growth east Lombok district ,research result is the average of contribution growth rate of fund balance toward economic growth (PDRB) on base constant price year 2010, east Lombok district year 2010-2016 is 9.85% and current prices is 11.36 % means that contribution fund balance toward rate of economic growth for five years in east Lombok district is significant enough.